KEHIDUPAN PETANI CAP TIKUS DI KELURAHAN RURUKAN KOTA TOMOHON - Wowor, Riko Ridel; Matheosz, Jenny Nelly; Deeng, Djefry (HOLISTIK, Journal Of Social and Culture, 2020)
Indonesia is a country that is crossed by the equator which makes this country a tropical climate. This gives its own advantages for the people of Indonesia because it is easier to work as a farmer.Palm tree or palm (Arenga pinnata, Arecaceae tribe) is the most important palm after coconut because it is a multipurpose plant. In North Sulawesi this plant is very easy to find because it has climatic and soil conditions that are in accordance with the requirements for growing sugar palm. Palm juice from palm trees is processed by traditional distillation to produce Cap Tikus.The Cap Tikus farmers used to be vegetable farmers who made use of palm trees that grew a lot in Rurukan, the juice of palm trees made of processed brown sugar as additional income for vegetable farmers. Making brown sugar takes a lot of time and energy, so farmers who have the knowledge to produce Cap Tikus choose to switch to making Cap Tikus products as the main source of livelihood because the manufacturing process is fast and easy to do. Cap Tikus farmers have an income that can support family life and better finance children's education, because there are farmers who are able to finance children's education up to tertiary institutions. The income of the farmers adjusts to the needs of the family and depends on the juice of the sugar palm trees produced, and how farmers sell their Cap Tikus.Â Keywords: farmer, palm, plant